THE GUARANTEE OF THE RIGHT TO FAMILY REUNION OF VENEZUELAN IMMIGRANTS AND REFUGEES FROM DOURADOS IN THE STATE OF MATO GROSSO DO SUL - Zanoni da Silva, João Lucas (2022)
The municipality of Dourados, located in the state of Mato Grosso do Sul, is the fourth largest recipient of Venezuelan immigrants and refugees interiorized in Brazil. The voluntary and assisted relocation of these people in this location occurred, for the most part, through the actions implemented by Operation Shelter and Project Shelter. Until September 2022, 3.349 people from the Venezuelan population had already been relocated to Dourados, of which 2.612 had arrived in the locality through the process of interiorization through family reunification and social gathering, based on the concept of family based on affectivity. Thus, this study aims to analyze the right to family reunification of immigrants and refugees as a human and fundamental right, as well as the public policies implemented in the aforementioned municipality to guarantee them this right and promote their local integration into the host society. The research is justified by bringing an analysis of the access policy and implementation of the right to family reunion of these people, through the mentioned process, with a view to their local integration. Therefore, the deductive method is used, in a qualitative approach, in a basic research of bibliographic and documentary references to verify how the right to family reunion has been guaranteed to this group of Dourados. Finally, it appears necessary to develop a public policy at the three federal levels of government to ensure their local integration into the host society, since relocation by family reunification and social gathering are not enough.